Manten Tebu Ritual: Semiotic Interpretation of Sugarcane Harvest Tradition - Syahputra, Bambang Panca; Amri, Yusni Khairul (Universitas Pahlawan Tuanku Tambusai, 2025)
The Manten Tebu (Sugarcane Bride) ritual in Rejoso village is an annual event before sugarcane milling. This tradition, preserved since the Dutch colonial era, carries deep symbolic meaning for the agrarian community. This study, based on a Detik jatim article from May 26, 2025, employs the Riffaterre semiotic method to analyze the tradition’s symbols. Using descriptive qualitative analysis, the research finds that Manten Tebu expresses respect for sugarcane as a source of livelihood and fertility, and reflects the relationship between the sugar factory and farmers. Symbolic elements—such as sugarcane pairs as bride and groom, offerings, processions, and prayers—form a system of signs embodying community hopes for a successful milling season.